The similarity forms and invariant solutions of two-layer shallow-water equations - Teoman, Özer; Nalan, Antar (Elsevier BV, 2008)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: two-layer shallow-water equations; Water waves, gravity waves; dispersion and scattering, nonlinear interaction; Symmetry analysis, Lie group and Lie algebra methods applied to problems in fluid mechanics; Dimensional analysis and similarity applied to problems in fluid mechanics; similarity solutions; gravity currents; symmetry groups